Brand Reputation and Emotional Attachment of Customers in Selected Quoted Deposit Money Banks in Asaba, Delta State, Nigeria - Okolie, Ugo Chuks; ERAKPOTOBO, Oyovwevotu Vincent (The International Journal of Business Review (The Jobs Review), 2023)
The purpose of this study is to look at the impact of brand reputation on customer emotional attachment in a few selected quoted deposit money banks in Asaba, Delta State, Nigeria. In order to investigate the variables, the study used a cross-sectional survey. The primary source of data was a self-administered questionnaire that yielded 73 valid responses. The Spearman correlation and multiple regression statistics were used to assess the hypotheses. The tests were conducted with a 95% confidence interval and a significance level of 0.05. Customers' emotional attachment to selected quoted deposit money banks in Asaba, Delta State, Nigeria is favorably and considerably influenced by brand reputation, according to the findings of the study. The research also found that good brand satisfaction, affection and identification were associated with quoted deposit money banks in Asaba, Delta State. The study suggests, among other things, that bank executives ensure that they can be easily distinguished from their competitors by carefully crafting an identity that is distinct from their competitors' and clearly communicating their performance history and reputation to customers and the general public.